Ice balance modeling in the Arctic Ocean in 1979–2019 - I. E. Frolov; M. Yu. Kulakov; K. V. Filchuk (Лëд и снег, 2022)
The results of numerical experiments on the model of joint water and ice circulation for the period from September 1979 to December 2019, aimed at studying the interannual variability of the ice balance in the Arctic Ocean, are considered. The results obtained made it possible to analyze the geographical features of the processes of ice formation and melting in the Arctic Ocean and to identify key areas that determine the volume of ice in the ocean. It is established that the main quantity of ice is formed in waters of the Siberian seas, and the most intense melting occurs in the North European Basin, where the ice transported by the Transpolar Current through the Fram Strait enters the relatively warm water of the Greenland Sea, heated by the North Atlantic Current. The formation of the absolute minimum of ice coverage in 2012 was promoted by the anomalous position of the anticyclonic hydrological cycle – much closer to the Canadian coast. This resulted in the fact that only a small part of the ice formed in the Siberian seas was involved into a weakened circulation, while most of the ice in the stream of the Transpolar Current was transported through the Fram Strait to the Greenland Sea. Statistical analysis of the results of numerical experiments demonstrated that the trend towards a decrease in the volume of ice in the Arctic Ocean is primarily determined by the global warming, and dynamic forcing exerts significant effect on local extremes.